2000
DOI: 10.1034/j.1600-0854.2000.010205.x
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Distinct Compartments in Polarized Madin–Darby Canine Kidney (MDCK) Cells for Membrane‐Volume Sorting, Polarized Sorting and Apical Recycling

Abstract: Previous studies of fibroblasts have demonstrated that recycling of endocytic receptors occurs through a default mechanism of membrane-volume sorting. Epithelial cells require an additional level of polar membrane sorting, but there are conflicting models of polar sorting, some suggesting that it occurs in early endosomes, others suggesting it occurs in a specialized apical recycling endosome (ARE). The relationship between endocytic sorting to the lysosomal, recycling and transcytotic pathways in polarized ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
183
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(202 citation statements)
references
References 52 publications
18
183
1
Order By: Relevance
“…After arrival at the cell surface, apical and basolateral membrane proteins are internalized into separate apical sorting endosomes and basal sorting endosomes (Figure 2), (Breitfeld et al, 1989;Mostov et al, 2003;Rodriguez-Boulan et al, 2005), mixed in common recycling endosomes and sorted into distinct recycling routes back to their original PM domain. The apical recycling route includes the apical recycling endosome (Apodaca et al, 1994;Brown et al, 2000). More recent work has shown that some newly synthesized PM proteins move from TGN to common recycling endosomes and are sorted there in not fully polarized MDCK cells (Futter et al, 1995;Leitinger et al, 1995;Orzech et al, 2000;Ang et al, 2004;Cancino et al, 2007;Gravotta et al, 2007; reviewed by Ellis et al, 2006 Figure 1 The epithelial polarity program (EPP).…”
Section: Polarized Trafficking Machinerymentioning
confidence: 99%
“…After arrival at the cell surface, apical and basolateral membrane proteins are internalized into separate apical sorting endosomes and basal sorting endosomes (Figure 2), (Breitfeld et al, 1989;Mostov et al, 2003;Rodriguez-Boulan et al, 2005), mixed in common recycling endosomes and sorted into distinct recycling routes back to their original PM domain. The apical recycling route includes the apical recycling endosome (Apodaca et al, 1994;Brown et al, 2000). More recent work has shown that some newly synthesized PM proteins move from TGN to common recycling endosomes and are sorted there in not fully polarized MDCK cells (Futter et al, 1995;Leitinger et al, 1995;Orzech et al, 2000;Ang et al, 2004;Cancino et al, 2007;Gravotta et al, 2007; reviewed by Ellis et al, 2006 Figure 1 The epithelial polarity program (EPP).…”
Section: Polarized Trafficking Machinerymentioning
confidence: 99%
“…This compartment was enriched in TfR and did not contain EEA1, a marker of early sorting endosomes (Wilson et al, 2000), or Rab11, a marker of AREs in MDCK cells (Casanova et al, 1999;Wang et al, 2001; Figure 2A). All of these characteristics are typical of a compartment denominated common RE, involved in the recycling of TfR and LDLR to the basolateral membrane and in the transcytosis of Polymeric IgA Receptor to the apical membrane via ARE (Futter et al, 1998;Brown et al, 2000;Wang et al, 2000). Additional experiments showed that the compartment decorated by 1Bn-Ab, unlike the TGN, was insensitive to tubulation induced by a kinase-dead form of PKD (Figure 3), a protein recently implicated in the regulation of the trafficking of basolateral proteins (Yeaman et al, 2004).…”
Section: Tgn-vs Ap1b-mediated Sorting Pathwaysmentioning
confidence: 99%
“…MDCK and PTR-MDCK cells (MDCK coexpressing rabbit pIgR and hTfnR; Brown et al, 2000;Wang et al, 2000) were cultured routinely in 10-cm dishes, in minimal essential medium (MEM, Biological Industries) containing 5% fetal calf serum (Biological Industries) and 1% antibiotics (Biological Industries). To induce polarity, cells were cultured on polycarbonate filter supports (0.4-m pore size, Transwell, Costar, Cambridge, MA) for 4 d before each experiment (Aroeti et al, 1993).…”
Section: Cell Culturementioning
confidence: 99%
“…In the course of transcytosis, pIgRdIgA complexes traverse various endosomal compartments, among which is an endocytic compartment located immediately underneath the apical surface (Gibson et al, 1998). This apical compartment, defined as apical recycling endosomes (AREs), is enriched in dIgA and is relatively deficient in recycling transferrin (Apodaca et al, 1994;Barroso and Sztul, 1994;Brown et al, 2000). AREs are thought to play a unique role in transcytosis, possibly by exploiting apical recycling mechanisms to shuttle transcytotic cargo to the apical surface.…”
Section: Introductionmentioning
confidence: 99%